2018
DOI: 10.1002/ddr.21481
|View full text |Cite
|
Sign up to set email alerts
|

Thiazole‐substituted benzoylpiperazine derivatives as acetylcholinesterase inhibitors

Abstract: Hit, Lead & Candidate Discovery After acetylcholine is released into the synaptic cleft, it is reabsorbed or deactivated by acetylcholinesterase (AChE). Studies on Alzheimer's disease (AD) in the mid‐20th century proved that cognitive dysfunctions are associated with cholinergic neurotransmission. Drugs, such as tacrine, rivastigmine, donepezil, and galantamine are known as acetylcholinesterase inhibitors. However, these drugs have limited use in advanced AD and dementia. Recently, the anticholinesterase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…Hence, medicinal chemists have made great effort to develop new AChE‐Is (Gao et al, ; Nygaard, ; Sahin et al, ). These efforts have ranged from slight structural modifications of the endogenous substrate of AChE (Bermúdez‐Lugo, Rosales‐Hernández, Deeb, Trujillo‐Ferrara, & Correa‐Basurto, ; Zemek et al, ) to the design and study of more complicated molecular structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, medicinal chemists have made great effort to develop new AChE‐Is (Gao et al, ; Nygaard, ; Sahin et al, ). These efforts have ranged from slight structural modifications of the endogenous substrate of AChE (Bermúdez‐Lugo, Rosales‐Hernández, Deeb, Trujillo‐Ferrara, & Correa‐Basurto, ; Zemek et al, ) to the design and study of more complicated molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the activity of this neurotransmitter in the brain is downregulated by the hydrolytic action of cholinesterases, particularly acetylcholinesterase (AChE) and also butyrylcholinesterase. Therefore, one of the main approaches for the palliative treatment of AD is still the use of AChE inhibitors (AChE-Is) (Gao, Tang, Liu, Liu, & Liu, 2019;Greig, Reale, & Tata, 2013;Herrmann, Chau, Kircanski, & Lanctôt, 2011;Hugo & Ganguli, 2014;Nygaard, 2013;Sahin et al, 2018), despite the increasing number of other strategies for treating AD that have led to drug design and development (Herrmann et al, 2011;Hugo & Ganguli, 2014;Nygaard, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As in our previous study, aryl piperazine derivatives were used as starting materials. First, the selected secondary amines were converted to the corresponding thioureide compounds ( A ) with benzoyl chloride/ammonium thiocyanate and reacted with α‐bromoacetophenone derivatives ( B ) to provide the final 2,4,5‐thiazole compounds ( 1‐44 ).…”
Section: Resultsmentioning
confidence: 99%
“…The IC 50 values were also calculated as 0.950μM for compound 4 and 2.104μM for compound 37 . When the chemical structures of these compounds were evaluated, the methoxy substituent on the phenyl ring linked to the piperazine structure had attracted attention, and this substituent was revealed in all compounds whose IC 50 value was calculated. Especially, compounds 5 , 16 , 27 , and 38 containing 4‐methoxyphenyl exhibited the highest enzyme inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation